Model Rehabilitation of Drug Addicts Based on Legal and Community Health Approaches to Promote Healthy Behavior - Chaidar, Muhamad; Septian Mubarrok, Alik (Journal of Law, Politic and Humanities, 2025)
The handling of drug addicts in Indonesia still faces serious problems due to the disharmony between legal norms that emphasize rehabilitation and law enforcement practices that tend to be repressive. The aim of this research is to analyze the normative framework for the rehabilitation of drug addicts, identify the barriers to implementation in the field, and formulate a model of integrative rehabilitation based on law and public health. This study employs a normative method with a legislative and conceptual approach. The results indicate that the Narcotics Law has provided a legal basis for rehabilitation; however, its implementation is not optimal due to limited resources, the repressive paradigm of law enforcement officers, societal stigma, and weak inter-agency coordination. Analysis using progressive legal theory and public health perspective emphasizes that addicts should be viewed as victims entitled to recovery, not merely as offenders. An integrative rehabilitation model that combines the roles of law and public health serves as a strategic solution to promote the protection of human rights, reduce the social impact of narcotics, and rehabilitate addicts towards healthy living behaviors.